EFEKTIVITAS PSIKOEDUKASI MORAL ENGAGEMENT DI SMA MUHAMMADIYAH 3 TULANGAN DALAM MENURUNKAN BULLYING PADA SISWA - Zidan, Muhammad Zidanil Ilmi Naf'an Munif; Laili, Nurfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to measure the effect of moral engagement psychoeducation on reducing bullying behavior among students at SMA Muhammadiyah 3 Tulangan. The research method used was quantitative experimentation with a student population of 35 people. The sampling technique used is saturated sampling. The scale used to measure bullying behavior is a pre-test and post-test scale compiled by researchers, while to measure moral engagement the Comprehensive School Climate Inventory (CSCI) is used. The analysis technique used is paired sample t-test using JASP software version 0.18. The research results showed that there was a significant difference between the pre-test and post-test results after being given moral engagement psychoeducation (t(34) = -5.619; p < 0.001). These results prove that moral engagement psychoeducation can reduce bullying behavior in students and increase moral engagement in the school environment.